Design of Scheduled Fog Irrigation System with ESP 32 in Mustard Seedbed (Brassica juncea L.) - Sumarsono, Joko; Widhiantari, Ida Ayu; De Side, Gagassage Nanaluih; Widhiantara, I Ketut Manik (The University of Lampung, 2024)
Plants receive water from the fog irrigation system in the form of tiny, mist-like water particles. Currently, irrigation technology has advanced, nurseries can be automatically irrigated. In this research, the ESP32 microcontroller is used to create the electronic circuits for the automation of the fog irrigation control system in a mustard green nursery. This study's methodology combines direct field observation with an experimental or trial approach. Water flow (ml/minute), water use efficiency (%), plant height (cm), number of leaves, and scheduled fog irrigation system performance are among the measured parameters. In this investigation, four different treatments were used: manual irrigation using a watering can, two-time, three-time, and one-time irrigation. All is going according to plan with this mist watering system. With an average height of 4.58 cm and an average number of leaves of 3.24, the mist irrigation system had the highest water use efficiency of 77.35% during the test. It was also found that mist irrigation produced the highest amount of mustard leaves in the three-times-per-day treatment. Keywords: ESP32, Fog irrigation, Green mustard, Nurseries.